MODEL PEMBELAJARAN INTERNALISASI IMAN DAN TAQWA DALAM PEMBELAJARAN PAI UNTUK USIA SEKOLAH DASAR - Supriyadi, Tedi (Mimbar Sekolah Dasar, 2016)
Learning by a teacher needs touches all dimensions of humanity that includes spirit, mind, heart, passion and physical balanced. Based on these dimensions, namely: the soul (transcendent must be turned on), reasonable (rational must be taught), heart (surrender must be strengthened), lust (self-fulfillment to be controlled), and physically (ready to act should be actualized), needs to be grown through the learning model TADZKIROH (Tunjukan teladan, Arahkan, Dorongan, Zakiyah (Kesucian), Kontinuitas, Repetisi, Organisasikan,  Hati). So that the behavior reflects the faith and piety in the stage of primary school age can reflect as accustomed to have a prayer, always acts like respect for parents, teachers and friends used to run the religious orders, used to read and study the scriptures and also undertake activities that benefit the world hereafter.Keywords: teaching model, internalization, iman, taqwa, tadzkiroh.